Genetic loss of GluN2B in D1-expressing cell types enhances long-term cocaine reward and potentiation of thalamo-accumbens synapses. (November 2018) - Joffe, Max; Turner, Brandon; Delpire, Eric; Grueter, Brad
Abstract Transient upregulation of GluN2B-containing NMDA receptors (R) in the nucleus accumbens (NAc) is proposed as an intermediate to long-term AMPAR plasticity associated with persistent cocaine-related behaviors. However, cell type- and input-specific contributions of GluN2B underlying lasting actions of cocaine remain to be elucidated. We utilized GluN2B cell type-specific knockouts and optogenetics to deconstruct the role of GluN2B in cocaine-induced NAc synaptic and behavioral plasticity. While reward learning was unaffected, loss of GluN2B in D1 dopamine receptor-expressing cells (D1) led to prolonged retention of reward memory. In control mice, prefrontal cortex (PFC)-D1(+) NAc AMPAR function was unaffected by cocaine exposure, while midline thalamus (mThal)-D1(+) NAc AMPAR function was potentiated but diminished after withdrawal. In D1-GluN2B−/− mice, the potentiation of mThal-D1(+) NAc AMPAR function persisted following withdrawal, corresponding with continued expression of cocaine reward behavior. These data suggest NAc GluN2B-containing NMDARs serve a feedback role and may weaken reward-related memories.